(untitled) (Journal of Hama University, 2025)
Soil salinity is a major factor that leads to low productivity of cultivated crops. Salinity causes oxidative stress In plants by enhancing the production of reactive oxygen species. Ascorbic acid is an effective antioxidant that is essential for increasing the salt tolerance of plants. However, plant antioxidant responses to salinity vary widely in tobacco plants. The current study was conducted to determine the effect of ascorbic acid on the tobacco plant (Basma). Which grows under salt water (12, 16 and 18 mm/cm2). Different concentrations of ascorbic acid (150, 300 and 450 mg/L) were applied. Salt toxicity significantly reduced the growth of tobacco plants. The significant decrease in chlorophyll and carotenoids due to salinity was mitigated by the use of ascorbic acid. Which contributed to improving the plant’s content of proline, hydrogen peroxide, and soluble sugars. Among the concentrations, 150 ml/L mm was most effective in reducing salinity stress. Therefore, we can recommend spraying with ascorbic acid which improved the growth of tobacco plants under saline conditions.